Development and characterization of a pseudo multiple reaction monitoring method for the quantification of human uromodulin in urine. (June 2016) - Hammond, Thomas G; Moes, Suzette; Youhanna, Sonia; Jennings, Paul; Devuyst, Olivier; Odermatt, Alex; Jenö, Paul
Background: Uromodulin is the most abundant protein in healthy human urine. Recently it has been suggested as a specific biomarker of renal tubular damage. We have developed a novel pseudo multiple reaction monitoring (pseudo MRM) for the protein's quantification in human urine.Results: Selection of two peptides allowed quantification of uromodulin in human urine. The pseudo MRM quantified uromodulin in healthy individuals between 21 and 1344 nM and in autosomal dominant tubulointerstitial kidney disease- UMOD patients between 2 and 25 nM.Conclusion: The pseudo MRM allows greater confidence in assay specificity than traditional MRM methods and quantified uromodulin at concentrations higher than achievable by ELISA. Differences in urinary uromodulin concentration related to the rs4293393 promoter variant in the UMOD gene was confirmed. This method will be used to further investigate uromodulin as a biomarker of renal injury.